Active Compound of Red Betel (Piper Crocatum Ruiz & Pav) as Activator of Cu/Zn Superoxide Dismutase in Silico - Riska Susila Putri; Mega Safithri; Dimas Andrianto (Indonesian Journal of Applied Research (IJAR), 2022)
Cancer degenerative disease is a serious problem in Indonesia, caused by free radicals, and can be prevented by antioxidant compounds. Superoxide dismutase (SOD) is the strongest enzyme that acts as a protective organism against oxidative stress. The active compound of red betel can be studied in silico as an activator of the SOD enzyme. Molecular docking visualization, physicochemistry, toxicity of red betel active compounds were studied and continued with molecular docking. The studied parameters were Gibbs free energy (ΔG) and receptor-ligand chemical bonding analysis. The test results show that the active compounds of red betel 6-Amino-2-(3-aminopropylamino)-9-(cyclohexylmethyl)- 2,3,4,5,6,7-hexahydro-1H-purin-8-one was well-absorbed dan safe for consumption with Gibbs free energy value of -9.1490 kcal/mol. Hydrogen and hydrophobic interactions of these compounds were similar to the control ligand, namely β-amyrin and Trehalose. This study concluded that the active compound of red betel 6-Amino-2-(3-aminopropylamino)-9-(cyclohexylmethyl)- 2,3,4,5,6,7-hexahydro-1H-purin-8-one has the best potential to increase the work of Cu/Zn-SOD enzymes. This compound also meets the requirements of Lipinski regulations so that it can be well absorbed orally by the body and is not carcinogenic